Pre-Targeting Bispecific Antibody (BSAB) and Pegylated Liposomal Drug Nanocarrier as Management of Acute Lymphoblastic Leukemia (ALL) In Pediatrics - Mareska, Viona; Halim, Wilson; Sadeva , Gede Krishna Arim (Green Publisher Indonesia, 2025)
Acute lymphoblastic leukemia (ALL) is a neoplastic condition commonly found in pediatric patients especially that involve B cell (B-ALL). Current treatments revolve around immunotherapy approaches such as Chimeric-Antigen Receptor T-cell (CAR-T) and tyrosine kinase inhibitor (TKI). However, flaws in both methods such as low pharmacokinetics, technical limitations, inability to recognize more than one antigen and other side effects remain a predicament to be solved. “immunotherapy”, “pediatry”, “b-all”, “bispesific antibody” and “PEGylated liposomal” were the keywords applied to scientific online databases, such as ScienceDirect, PubMed, dan Researchgate. A total of 25 journals were screened, reviewed and utilized with utmost precision to construct a literature review. Preparation of targeting bispesific antibody (BsAb) is constructed through the formation of chemical bond between the anti-mPEG scFV and CD20, whereas PEGylated liposomal drug nanocarriers is prepared through a covalent bonding chemical reaction. PEGylated drug nanocarriers has nontoxic, immunogenicity, antigenicity, and long half-life properties that increases both the pharmacokinetics and pharmacodynamics of anticancer drugs like chemotherapy through increased distribution, accumulation and decrease elimination of the drugs. BsAb will specifically target cancer-specific antigens, such as CD20 in cancer cells to initiate adaptive immune responses. Additionally, the antibody dependent endocytosis properties are a vital part in cancer therapy to increase cellular uptake of the liposome. All in all, the combination of bispesific antibody (BsAb) PEGylated liposomal drug nanocarriers towards B-ALL shows great promise towards the management of B-ALL in pediatric patients.